GREENHOUSE DESIGN CONCEPTS FOR MOON AND MARS - Imhof, Barbara; Hogle, Molly; Hoheneder, Waltraut; Waclavicek, René; Davenport, Bob; Schubert, Daniel; Vrakking, Vincent; Zeidler, Conrad; Maiwald, Volker; Zabel, Paul; Dorn, Markus; Fiore, Lorenzo; et al. (2019)
This paper will show the methodology used for developing a greenhouse design concept for moon and Mars, derived from the EDEN ISS simulation facility in Antarctica. This document details the preliminary design of a future planetary greenhouse, adapted from the Mobile Test Facility (MTF) which was built and operated as part of the EDEN ISS project. Lessons learned from the Antarctic operations phase, as well as references to existing mission scenarios were considered for establishing system requirements. Based on these requirements, a preliminary design of the greenhouse structure, and plant cultivation subsystems was developed. The preliminary design presented in this document is a deployable cylindrical structure, with rigid end caps and an inflatable membrane shell. The structure has been sized to fit within the payload fairing of a Falcon 9 launcher (or similar), with a stowed configuration diameter of 4 meters and a length of 6.3 meters. Following deployment, the structure is envisioned to be 12.9 meters long and the membrane shell will expand to a diameter of 5 meters. An estimation of the subsystem volumes was made in order to design the internal configuration. This internal layout offers 30.8 m² of cultivation area, a more than twofold increase over the existing Mobile Test Facility. Differences and similarities between the two facilities are discussed.